Figure of an Ascetic with long beard - Temples of India Project Team (Jio Institute, 2024)
The ascetic is shown on one of the pillars with a long beard and what seems like a jata (matted hair). A kamandala (water carrier) is slung over one of his shoulders with a rope. He is depicted wearing nothing but a kopina (loincloth) and the janeyu (sacred thread), which is prominently displayed. The presence of the janeyu signifies the Brahmin lineage of ascetics in the Pashupata sect, tracing back to Lakulisa and his four disciples. Lakulisa himself is depicted elsewhere in this temple with a prominent janeyu. The minimalist clothing and kamandalu symbolize his asceticism.